Teachers’ Strategies in Providing Immediate and Delayed Corrective Feedback in EFL Speaking Class - Dzul Qorihah; Syafi’ul Anam; Ahmad Munir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Speaking remains one of the most challenging skills for Indonesian EFL learners, especially at the senior high school level. Frequent grammatical, lexical, and pronunciation errors are often inconsistently corrected, affecting learners’ long-term speaking development. Teachers thus face a pedagogical dilemma in deciding whether to provide Oral Corrective Feedback (OCF) immediately during speech or after the activity. This study investigates teachers’ strategies in delivering immediate and delayed OCF during speaking lessons involving descriptive text tasks. Using a qualitative case study design, two English teachers from a senior high school in East Java, Indonesia, were observed across four classroom sessions and interviewed twice. Data were analyzed thematically and interactionally. The findings reveal that teachers adjusted feedback timing based on instructional goals, students’ affective conditions, and task complexity. For example, immediate feedback was applied when repeated grammatical errors disrupted meaning, while delayed feedback was used after presentations to preserve fluency and confidence. Teachers also demonstrated reflective decision-making by modifying feedback timing during lessons when similar errors persisted. These results highlight the importance of flexible, student-responsive, and reflective feedback practices for effective EFL speaking instruction.